Free and Bioavailable 25-Hydroxyvitamin D Concentrations are Associated With Disease Activity in Pediatric Patients With Newly Diagnosed Treatment Naïve Ulcerative Colitis. Issue 3 (16th February 2018) - Sauer, Cary G; Loop, Matthew S; Venkateswaran, Suresh; Tangpricha, Vin; Ziegler, Thomas R; Dhawan, Ashish; McCall, Courtney; Bonkowski, Erin; Mack, David R; Boyle, Brendan; Griffiths, Anne M; Leleiko, Neal S; et al.
Abstract: Background: Vitamin D regulates intestinal epithelial and immune functions, and vitamin D receptor deficiency increases the severity of murine colitis. Bioavailable 25-hydroxyvitamin D (25(OH)D) is available to target tissues and may be a driver of immune function. The aim is to evaluate the relationship of bioavailable 25(OH)D to the clinical expression of treatment naive pediatric ulcerative colitis (UC). Methods: The PROTECT (Predicting Response to Standardized Pediatric Colitis Therapy) study enrolled children ≤17 years newly diagnosed with UC. Free and total 25(OH)D were directly measured and 25(OH)D fractions were compared with disease activity measures. Results: Data were available on 388 subjects, mean age 12.7 years, 49% female, 84% with extensive/pancolitis. The median (IQR) total 25(OH)D concentration was 28.5 (23.9, 34.8) ng/mL, and 57% of subjects demonstrated insufficient vitamin D status (25(OH)D < 30 ng/mL). We found no evidence of association between total 25(OH)D and disease activity. Regression models adjusted for age, sex, race, and ethnicity demonstrated that an increase from 25 th to 75 th percentile for bioavailable and free 25(OH)D were associated with a mean (95 th CI) decrease in the Pediatric Ulcerative Colitis Activity Index (PUCAI) of -8.7 (-13.7, -3.6) and -3.1 (-5.0, -1.2), respectively. No associations were detected between 25(OH)D fractions and fecal calprotectin or Mayo endoscopy score. Conclusions: Vitamin D insufficiency is highly prevalent in children with newly diagnosed UC. We found associations of free and bioavailable, but not total 25(OH)D, with PUCAI. Bioavailable vitamin D may contribute to UC pathophysiology and clinical activity.